2012
DOI: 10.1118/1.4735268
|View full text |Cite
|
Sign up to set email alerts
|

SU‐E‐T‐207: Flatness and Symmetry Threshold Detection Using Statistical Process Control

Abstract: X-bar/R charts of SCC can detect exceptional variation prior to exceeding the beam uniformity criteria set forth in AAPM TG-142. The high level of PCC sensitivity to change may result in an alarm when in fact minimal change in beam uniformity has occurred. Further study is needed to determine if a combination of individual SCC alarms would reduce the false positive rate for beam uniformity intervention. This project was supoorted by a grant from Varian Medical Systems, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…SPC techniques can offer a solution in identifying variation within a process [4][5][6][7][8][19][20][21][22][23]25,28,[34][35][36][37][38][39][40][41]. Statistical and graphical analysis using SPC metrics revealed that each performance parameter had its own operating window in which operational consistency of linacs was maintained.…”
Section: Discussionmentioning
confidence: 99%
“…SPC techniques can offer a solution in identifying variation within a process [4][5][6][7][8][19][20][21][22][23]25,28,[34][35][36][37][38][39][40][41]. Statistical and graphical analysis using SPC metrics revealed that each performance parameter had its own operating window in which operational consistency of linacs was maintained.…”
Section: Discussionmentioning
confidence: 99%
“…While I/MR charts are the most sensitive in identifying changes in parameters, our methods for calculating the chart limits and chart analysis rules will determine how effective we can predict when maintenance intervention is necessary. Our experience has shown that the use of traditional SPC chart limits (±3 standard deviation (±3 σ ) from the grand mean) can result in an unacceptable rate of false positive signals [ 5 , 6 ]. Using information on system specifications from the manufacturer, consulting the literature for recent studies on quality control of complex treatment delivery [ 16 , 17 ] (IMRT, VMAT, SBRT, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…Our hybrid method for calculating the chart limits and chart analysis rules will determine how effective we can predict when maintenance intervention is necessary. Our experience has shown that the use of traditional SPC chart limits (±3 standard deviation from the grand mean) can result in an unacceptable rate of false positive signals (1,2). Using information on system specifications from the manufacturer, consulting the literature for recent studies on quality control of complex treatment delivery (IMRT, VMAT, SBRT, etc) and white papers on quality assurance of linear accelerators (3) we introduce a hybrid approach to calculating the control chart limits that includes a factor (S p ) that fractionally increases the limits based on the operational parameter specification and/or performance criteria.…”
Section: Methodsmentioning
confidence: 99%